STUDY ON DYNAMIC CHARACTERISTICS OF END-TOOTHED CONNECTION ROTOR CONSIDERING CONTACT EFFECT - YANG ZhengLie; WANG AiLun; ZHANG HaiBiao; MA Wu; WANG Hai (Jixie qiangdu)
Aiming at the problem that the finite element analysis software can’t deal with the nonlinear characteristics such as elastoplastic element in modal analysis,the static finite element analysis method is used to obtain the variation of the stiffness of the end tooth structure considering the surface contact with the preload force and proposed an equivalent method that can characterize the contact effect on the stiffness of the end tooth joint structure.An equivalent model of the end-toothed rotor considering contact is established.The influence of preload force on the modal and critical speed of the rotor is obtained by the modal analysis of the rotor under different preload conditions.Analysis data indicates that the equivalent method can correctly reflect the influence of contact effect on rotor stiffness in modal analysis,and the accuracy meets the requirements of engineering application.